THE EFL STUDENTS' STRATEGIES IN LEARNING ENGLISH SPEAKING KILLS :A descriptive study at the Tertiary level - Natalia, - (2008)
This current research investigated the EFL students' strategies to learn English speaking skills and the application of the strategies. The sample of the research was 30 fourth grade university students of English major. To identify the wide range of the students' strategies, SILL (Strategies Inventory for Language Learning) was administered. The students were asked to check their own frequency of use of each strategy. Meanwhile, group interview was designed to reveal the ways the strategies were applied to learn vocabulary, pronunciation, grammar and enhance speaking fluency and comprehension. It was revealed that the students used social, compensation and metacognitive strategies more frequently than cognitive and memory strategies and likely infrequently used affective strategies. The frequently used types of strategies they used were strategies which involved active use of English and directly helped the students to overcome their speaking skills inadequacy. The strategies use was influenced by students' characteristics. The students applied appropriate strategies which fit the speaking skills requirements. The strategies were applied in a relevant ordered manner.